PERENCANAAN ULANG STRUKTUR GEDUNG SMA NEGERI 1 LUBUK SIKAPING KABUPATEN PASAMAN - Putra, Randi; Masril, Masril; Susanti Yusman, Ana (Ensiklopedia Research and Community Service Review, 2024)
In line with the development of Science and Technology (IPTEK), especially in the field of Civil Engineering, building construction is currently also developing very rapidly. In the construction of a building, construction must be produced with sufficient capacity, good quality and efficient implementation. In West Sumatra itself, the need for housing and office buildings as well as the construction of educational facilities is currently experiencing very rapid development. Like the "SMA N 1 Lubuk Suhuing Building" which aims to improve educational facilities and infrastructure. And for all of this, planning and building work are needed which must comply with standards, be safe and efficient. This research aims to plan the dimensions of structural elements, calculate structural reinforcement. The structural element data used is from the results of the preliminary design (Preliminary Design). The analysis was assisted by the SAP2000 Version 14 program by selecting a network system structure system (Grid System). Based on the results of Preliminary Design calculations, data was obtained for the use of the upper structure from the 1st floor to the 2nd floor, where the cross-sections of the main columns on the 1st floor measuring 45cm x 45cm and the 2nd floor measuring 40cm x 40cm, the main beams on the 1st floor and 2nd floor measuring 50cm x 25cm, floor slab planning and also Concrete tiles were carried out using Preliminary Design, resulting in a floor slab measuring 12 cm thick. Reinforcement used for beams D19 and D10, reinforcement for columns D19 and D12, reinforcement for floor slabs D10.Keywords : Preliminary design, SAP2000, Building Structures, Schools